2019
DOI: 10.1097/pas.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

SF3B1, NRAS, KIT, and BRAF Mutation; CD117 and cMYC Expression; and Tumoral Pigmentation in Sinonasal Melanomas

Abstract: Sinonasal melanomas encompass melanoma arising in the nasal cavity and paranasal sinuses. Despite recent advances in tumor genomics, correlation between mutational status and protein expression with prognosis and tumor pigmentation has not been carried out in sinonasal melanomas. Ninety-five sinonasal melanomas from 95 patients were included. As per univariate analyses, age was the only variable that significantly correlated with progression-free survival. SF3B1, NRAS, KIT, and BRAF mutations were documented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 48 publications
1
8
1
Order By: Relevance
“…Our cohort had one patient with a canonical –124C>T mutation and one patient with a –185C>G mutation, which was previously unknown. SF3B1 mutations, reported at low frequencies in other cohorts [11], were not present in our cohort. A study from Cosgarea et al investigate mucosal melanomas using a NGS panel including 15 head and neck primary tumors.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our cohort had one patient with a canonical –124C>T mutation and one patient with a –185C>G mutation, which was previously unknown. SF3B1 mutations, reported at low frequencies in other cohorts [11], were not present in our cohort. A study from Cosgarea et al investigate mucosal melanomas using a NGS panel including 15 head and neck primary tumors.…”
Section: Discussioncontrasting
confidence: 60%
“…Another group looks at 29 genes and finds alterations in mainly NRAS or KRAS , but no KIT mutation [10]. The most recent study analyzes a large cohort of 95 sinonasal melanomas [11]. However, only BRAF , NRAS , KIT and SF3B1 are investigated by Sanger sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Exon 15 BRAF V600E variant was most frequent in cutaneous melanoma with a UV signature [39,40,41]. Recently, some studies reported the prevalence of BRAF mutations as lower than 10% in SNM patients [24,42,43]. In the present study, data revealed that SNM lack the mutational signature of UV light, predominantly of transversion mutation, in overall genes tested, thus unveiling a different mutational signature between cutaneous and SNM subtypes.…”
Section: Discussionsupporting
confidence: 54%
“…In a large series of 706 mucosal melanomas, KIT and BRAF mutational status did not correlate with overall survival (OS); however, NRAS was not analyzed in this series [6]. Correlation between NRAS, BRAF and KIT mutations and survival was not observed in prior series of sinonasal melanomas [7,12]. KIT mutation has been reported to be a marker of better progression-free survival in vulvar melanomas [11].…”
Section: Introductionmentioning
confidence: 75%
“…In a series of 444 mucosal melanomas from a European population investigated by Sanger sequencing, NRAS, KIT and BRAF mutations were evenly distributed across the different mucosal melanoma subgroups [8]. The prognostic role of these commonly recurrent mutations in mucosal melanomas has only been studied in some series [6,7,11,12]. In a large series of 706 mucosal melanomas, KIT and BRAF mutational status did not correlate with overall survival (OS); however, NRAS was not analyzed in this series [6].…”
Section: Introductionmentioning
confidence: 92%